Student internship placement using personal decision aid / Anis Nabila Azizi and Azmi Abu Seman - Azizi, Anis Nabila; Abu Seman, Azmi (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Student Internship Placement using Personal Decision Aid is a web-based system that assist student, the internship coordinator as well as the organization. As university enrollment increased, the management of the internship program became out of control. Students who have been completing internships at UiTM Perlis using the manual approach have created a lot of issues. The biggest issue at UiTM Perlis is the manual management of the internship program, which is time-consuming, includes a lot of paper, and is poorly managed between coordinator and organization as well as students. To address the issue between students, the coordinator, and the organisation, the Student Internship Placement using Personal Decision Aid system was developed. This study aims to design and develop a personal decision aid to help the student select the ideal internship organizations. A complete and effective web-based system will be created using a waterfall model. Furthermore, functionality testing and usability testing were the two testing methods used to implement There were 31 respondents, including students, the internship coordinator, and the organization. The result showed that the Student Internship Placement using Personal Decision Aid system performed very well in terms of user interface satisfaction, usefulness, and usability as well as its use by users. As for future work, new researcher can add features that would allow the organization to choose the student based on their preferences as the opportunity for the company to approach the student about an internship when the student meets their requirements, including a chatbot functionality so that students may engage with the company directly and integrating email features so that students would receive notifications via email. In conclusion, the burden for those a part of the UiTM internship programme is effectively handled and minimized by this approach.